‘Incorporate into one body torne and scattered limmes’: Recontextualising Principal Navigations within the networks of Richard Hakluyt - Stevenson, E (2021)
Richard Hakluyt’s The Principal Navigations, Voyages, Traffiques and Discoveries of the English Nation (1589 and 1598-1600) was an enormously influential work in the development of travel writing and a formative influence on early modern English identity. Hakluyt drew on and developed a previously European mode to create his compendium, and Principal Navigations is now considered the prime source for sixteenth-century English travel writing, often regarded historically as an objective record. By illuminating and reconstructing the politicised textual network of creators and influences which lay behind the text and analysing the effect they had on Hakluyt’s editorial techniques, this thesis offers a new understanding of the intricate and fluid negotiations which shaped English identity and English political and mercantile agency in the early modern period.